Two abundant bioaccumulated halogenated compounds are natural products - Teuten, E. L.; Xu, L.; Reddy, C. M. (Science, 2005)
Methoxylated polybrominated diphenyl ethers (MeO-PBDEs) have been found bioaccumulated in the tissues of a variety of aquatic animals and at concentrations comparable to those of anthropogenic halogenated organic compounds, including polychlorinated biphenyls (PCBs). The origin of the MeO-PBDEs has been uncertain; circumstantial evidence supports a natural and/or an industrial source. By analyzing the natural abundance radiocarbon content of two MeO-PBDEs isolated from a True's beaked whale (Mesoplodon mirus), we show that these compounds were naturally produced.
Teuten, Emma LXu, LiReddy, Christopher MengResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, Non-P.H.S.2005/02/12 09:00Science. 2005 Feb 11;307(5711):917-20.